Room temperature deposition of functional ceramic films on low-cost metal substrate. Issue 14 (1st October 2018) - Khansur, Neamul H.; Eckstein, Udo; Benker, Lisa; Deisinger, Ulrike; Merle, Benoit; Webber, Kyle G.
Abstract: In various practical applications, such as high power actuators, high sensitivity sensors, and energy harvesting devices, polycrystalline piezoelectric films of 1–100 µm thickness and sizes ranging from several µm 2 to several cm 2 are required. With conventional film deposition processes, such as sol-gel, sputtering, chemical vapor deposition, or pulsed laser deposition, it is difficult to fabricate films with higher thickness due to their low deposition rate and high interfacial stress. The aerosol deposition method (AD), a relatively new deposition technique, can be used to fabricate highly dense thick films at room temperature by the consolidation of submicrometer-sized ceramic particles on various ceramic, metal, glass, and polymer substrates. Ferroelectric BaTiO3 ceramic films of different thicknesses ranging from 1 to 30 µm were fabricated on a low-cost metallic substrate at room temperature using the AD method. Surface morphology and adhesion of the film were analyzed. Analysis of internal residual stresses revealed an equibiaxial compressive stress state in the as-processed film. Electrical characterization of films annealed at 500 °C shows an enhanced polarization value of ~ 14 µC/cm 2 over that of the as-processed film. This improved property is related to the decreasing internal residual stress. In addition, the BT films prepared in this work were found to withstand electric fields greater than 100 kV/mm, which is possibly related to the inherent relatively defect-free structure of AD films.